Citral impairs intestinal changes caused by ulcerative colitis through modulation of antioxidant, anti-inflammatory and healing activities - Silva, Maycon Tavares Emílio; Rodrigues, Vinícius Peixoto; Ruiz-Malagon, Antonio J.; Guidolin, Isabela Galende; Dario, Felipe Lima; Fioravanti, Mariana Moraes; Rodriguez-Nogales, Alba; Gálvez, Julio; Lima, Clelia Akiko Hiruma (Springer Nature, 2025)
IntroductionUlcerative colitis (UC) is the main representative of inflammatory bowel diseases (IBD) are chronic conditions characterized by intestinal inflammation, caused by the overproduction of pro-oxidant species and an immune response that damages the gut mucosa.ObjectiveTo evaluate the anti-inflammatory and protective effect of Citral, a monoterpene, on in vitro and in vivo models of UC.MethodologyMale C57BL/6J mice were used for DSS 3%-induced UC for 5 days in drinking water. Concomitantly, daily oral citral (25, 100, and 300 mg/kg, p.o.) or vehicle was administered. Colonic segments were collected to evaluate neutrophil infiltration, lipid peroxidation, and the expression of antioxidant markers. NCM-356 and RAW-294 cells were stimulated with LPS (10 and 100 ng/mL, respectively). Cell viability, nitrite levels, scratch wound healing assay, and gene expression of inflammatory and growth factors were assessed.ResultsAcute treatment with citral (100 and 300 mg/kg) exhibited an anti-colitis effect by reducing the disease activity index (DAI) score compared to that in the DSS-vehicle group. This response was mediated by a significant reduction in myeloperoxidase activity and thiobarbituric acid reactive species levels, associated with an increase in superoxide dismutase activity, indicating anti-inflammatory and antioxidant activities (p < 0.05). The monoterpene reversed LPS-induced intestinal epithelial disturbance in the scratch wound healing process under different conditions and possibly reduced inos expression.ConclusionCitral treatment prevents the development of UC via anti-inflammatory, antioxidant, and healing effects.